2009
DOI: 10.5424/sjar/2009074-1096
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the prediction of apparent metabolisable energy content of starchy grains and cereal by-products for poultry from its chemical components, in vitro analysis or near-infrared reflectance spectroscopy

Abstract: Regression models including chemical composition, in vitro digestibility and near infrared reflectance spectroscopy (NIRS) were compared in order to predict the energy value of several feed ingredients for poultry. The nitrogen-corrected apparent metabolisable energy content (AMEn) in cockerels and its proportion on total gross energy (AMEn/GE) were determined in 94 batches from six starchy grains and six cereal byproducts. Two preliminary trials were also designed to adapt in vitro methods for prediction of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 19 publications
1
23
1
Order By: Relevance
“…These authors correlated the in vitro starch degradation rate (modified assay from [14]) in 12 feedstuffs with the in vivo jejunal and ileal starch digestion in broiler chickens, showing that a 2-h incubation correlated well with the jejunal starch degradation, whereas a 4-h incubation correlated with the ileal starch degradation (Figure 4). Their data seem conflicting with losada et al [11], who showed a lower in vitro organic matter digestibility in corn compared with wheat after short incubation times ( Figure 2). However, this observation might be related to corn characteristics (amylopectin-to-amylase ratio), as a slower in vitro starch degradation rate from waxy corn compared with normal corn was shown [3].…”
Section: In Vitro Assaysmentioning
confidence: 85%
See 4 more Smart Citations
“…These authors correlated the in vitro starch degradation rate (modified assay from [14]) in 12 feedstuffs with the in vivo jejunal and ileal starch digestion in broiler chickens, showing that a 2-h incubation correlated well with the jejunal starch degradation, whereas a 4-h incubation correlated with the ileal starch degradation (Figure 4). Their data seem conflicting with losada et al [11], who showed a lower in vitro organic matter digestibility in corn compared with wheat after short incubation times ( Figure 2). However, this observation might be related to corn characteristics (amylopectin-to-amylase ratio), as a slower in vitro starch degradation rate from waxy corn compared with normal corn was shown [3].…”
Section: In Vitro Assaysmentioning
confidence: 85%
“…In the first digestion step, samples were incubated with pepsin at pH 2, 39°C, over 2 h. The second step was incubation with pancreatin (protease, amylase, and lipase) at pH 6.8 and 39°C over 4 to 19 h. Finally, a third step was introduced using microbial carbohydrases (Viscozyme 120l [12]) at pH 4.8 and 39°C to simulate hindgut fermentation. The in vitro assay was calibrated with individually housed adult roosters fed mash diets near maintenance level [11]. Results (given in Figure 2) showed that the 2-step assay, using a 7-h incubation period with pancreatin, gave a good estimate of the relative in vivo AME n value of wheat, being 95% of the value of corn [11].…”
Section: In Vitro Assaysmentioning
confidence: 99%
See 3 more Smart Citations